1992
DOI: 10.1111/j.1365-2141.1992.tb06476.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thrombocytopenia in HIV‐infected and non‐HIV infected drug users and homosexual men

Abstract: We studied the prevalence and risk factors for thrombocytopenia among 299 drug users and 461 homosexual men. The prevalence of thrombocytopenia was 3.3% in HIV-negative homosexual men, 8.7% in HIV-negative drug users, 16.4% in HIV-positive homosexual men, and 36.9% in HIV-positive drug users. With multivariate logistic regression HIV-seropositivity (odds ratio 3.3), a history of injecting drugs (OR 3.9), an increased number of lymphocytes (OR 0.44), an increased number of neutrophils (OR 0.53) and a larger mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 20 publications
5
20
0
5
Order By: Relevance
“…/L, while 6 (3.3%) of intravenous drug users had a count of < 50 × 10 9 /L. 5 These differences may be explained, in part, by the higher incidence of co-infection with hepatitis C and underlying liver disease in HIV-infected intravenous drug users. 6 In a prospective multicenter cohort study of 738 HIVinfected hemophilia patients, the incidence over time of HIV-related conditions was determined in 130 children and 193 adults.…”
Section: Epidemiologymentioning
confidence: 83%
See 1 more Smart Citation
“…/L, while 6 (3.3%) of intravenous drug users had a count of < 50 × 10 9 /L. 5 These differences may be explained, in part, by the higher incidence of co-infection with hepatitis C and underlying liver disease in HIV-infected intravenous drug users. 6 In a prospective multicenter cohort study of 738 HIVinfected hemophilia patients, the incidence over time of HIV-related conditions was determined in 130 children and 193 adults.…”
Section: Epidemiologymentioning
confidence: 83%
“…22 Severe thrombocytopenia in patients with advanced HIV infection is frequently associated with additional cytopenias. [1][2][3][4][5][6] In a study of 52 HIV-infected intravenous drug users with thrombocytopenia, 4 patients (8%) with advanced HIV infection had a hypocellular bone marrow examination and pancytopenia. 19 HIV-infected drug users were also more likely to have antibodies to both hepatitis B and C and to have abnormal liver function studies.…”
Section: 18mentioning
confidence: 99%
“…For instance, it has been shown that 46% of critically ill medical and surgical patients have a platelet count lower than 150¥10 9 /L, 1 and that the prevalence of thrombocytopenia is 20% in patients with systemic lupus erythematosus, 2 37% in human immunodeficiency virus-positive drug users, 3 18% in patients with chronic active hepatitis B, and 13% in those with chronic hepatitis C. 4 In contrast, almost nothing is known about the prevalence of thrombocytopenia in the general population, although there is a general consensus that a low platelet count is recognized with increasing frequency in apparently healthy subjects, especially due to the measurement of platelet numbers as part of routine blood testing. 5,6 In some of these cases, further clinical investigation reveals that thrombocytopenia is secondary to an occult disease, while in others it is found that the low platelet count is inherited.…”
Section: Introductionmentioning
confidence: 99%
“…Según algunos estudios, esta trombocitopenia puede ser producida por la combinación de todos Anticuerpos antiplaquetarios en infección viral 1. los mecanismos patogénicos de destrucción plaquetaria expuestos inicialmente (33,34).…”
Section: Virus De La Inmunodeficiencia Humanaunclassified
“…La síntesis de anticuerpos antiplaquetarios en la infección por VIH-1, se ha explicado por medio de dos mecanismos; el primero es la activación policlonal de los linfocitos B por fallas del sistema inmunológico, que lleva a la producción de anticuerpos autorreactivos o autoanticuerpos (35-39), y la segunda explicación es la capacidad del VIH de integrarse a las plaquetas y a precursores megacariocíticos (33,38), que induciría el desarrollo de nuevos antígenos sobre la superficie de las plaquetas debido a la interacción de estructuras virales con estructuras plaquetarias, o modificaría la conformación de las glucoproteínas presentes en su membrana (exposición de antígenos plaquetarios crípticos). En ambos casos, el resultado sería la formación de autoanticuerpos dirigidos contra estos nuevos antígenos, según lo planteado por Ballem et al (38), lo cual conduciría a un secuestro prematuro de las plaquetas mediado por el sistema fagocítico mononuclear y su posterior destrucción (figura 1) (33-35).…”
Section: Virus De La Inmunodeficiencia Humanaunclassified